POLA PENGEMBANGAN PROGRAM SUASANA RELIGIUS MELALUI AKTUALISASI NILAI-AKTIVITAS DAN SIMBOL-SIMBOL ISLAMI DI MADRASAH - Fitriani, Mohamad Iwan (JURUSAN PENDIDIKAN AGAMA ISLAM, 2015)
Religious based education in Islamic education perspective is an educational institution which is built to actualize Islamic values. ThoseIslamic values are manifested in religious activities and symbols which aresupported by Islamic educational system that consists of input-process-output and outcome. This study is focused on: actualization of religious based education in islamic education management through vertical obedience values (devine values: faith and piety, charity, sincere, resignation, grateful and horizontal values obedience (human values: shilaturrahim, brotherhood, barakah, togetherness, work hard, consistence and patience). Thoose both values grow and create other values (scientific, economy, art and social values). Then, those values inspire religious daily, weekly, monthly, annually and accidentally activities and religious symbols such as Mosque, Islamic decorations made from Al Qurâan, Hadits and Islamic proverb. Islamic values, activities and symbols are essential elements of religious culture at any islamic educational institution. This study shows that islamic values need to be reelaborated to enrich islamic values implemented at madrasah run as well as possible.